MANFAAT LAYANAN KONSELING KELOMPOK DALAM MENYELESAIKAN MASALAH PRIBADI SISWA - Egy Novita Fitri; Marjohan Marjohan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
The importance of group counseling service in solving student’s problem is not demied. The purpose of this research is to reveal the advantage of group counseling service to solve student’s problem in privat, social, and study point of view. Results of this research show that students are agreed with some advantages in group counseling service that are: (1) solving student’s problem in privat aspect which is viewed from self, friendship, family aspects, (2) solving student’s problem in social aspect that viewed from interaction and adaptation with environment, (3) solving student’s problem from study aspect that viewed from aspects of completing tasks, motivation in learning, and god study manners.